Diabetes Self-Management and Quality of Life Adult People with Diabetes Mellitus Type 2: A Systematic Review - Mula Tarigan; Pulsuk Siripul; Bumpenchit Sangchart (Talenta Publisher, 2023)
One of the health problems currently faced globally and in Indonesia is type 2 diabetes because it presents a harmful impact on the sufferer, and the number continues to increase every year. Diabetes self-management programs are considered one activity that maintains the quality of life of type 2 diabetes patients. This systematic review aimed to determine the effectiveness of type 2 diabetes self-management programs on the quality of life of patients with type 2 diabetes. The databases used to search were CINAHL, Proquest, and PubMed, between 2006 and 2016, and all articles were evaluated for relevance and quality of research. There were 14 articles analyzed on the characteristics, content of interventions, quality of life instruments, and quality of life outcomes. Eleven of the 14 studies significantly showed an effect of diabetes management programs on the quality of life of patients with type 2 diabetes. Nurses and other health professionals can apply diabetes self-management programs at all levels of health care.